2001
DOI: 10.1097/00001756-200112210-00041
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitor NS398 preserves neuronal function after hypoxia/ischemia in piglets

Abstract: Anoxic stress attenuates NMDA-induced pial arteriolar dilation via a mechanism involving actions of cyclooxygenase (COX)-derived reactive oxygen species (ROS). We examined whether the selective COX-2 inhibitor NS398 would protect neuronal function after global hypoxia/ischemia (H/I) in piglets. Pial arteriolar responses to NMDA (10-100 micromol/l) were determined using intravital microscopy in anesthetized piglets before and 1 h after H/I. Study groups received vehicle, 0.3, 1, or 5 mg/kg NS398, or 0.3 mg/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…It seems likely that NMDA receptors are a primary target of ROS derived from COX metabolism of arachidonic acid as well as from damaged mitochondria after ischemia (22,24,30). Our studies showing that administration of structurally different inhibitors of COX (indomethacin and NS398) (4,12,18), as well as superoxide dismutase (4), is able to preserve NMDAinduced dilation following a variety of hypoxic/ischemic conditions provide support for the concept that superoxide formation via the COX pathway is a pivotal event in neuronal dysfunction under these conditions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It seems likely that NMDA receptors are a primary target of ROS derived from COX metabolism of arachidonic acid as well as from damaged mitochondria after ischemia (22,24,30). Our studies showing that administration of structurally different inhibitors of COX (indomethacin and NS398) (4,12,18), as well as superoxide dismutase (4), is able to preserve NMDAinduced dilation following a variety of hypoxic/ischemic conditions provide support for the concept that superoxide formation via the COX pathway is a pivotal event in neuronal dysfunction under these conditions.…”
Section: Discussionmentioning
confidence: 69%
“…Indomethacin, which decreases ROS production in newborn piglet brain after ischemia (2) and asphyxia (26), has been shown to preserve the NMDA response after asphyxia (12), ischemia (18), and hypoxia (4). Similar protective effects have been obtained following administration of superoxide dismutase (4) or the selective blockade of COX-2.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In our laboratory, the newborn piglet model has long been used to study the morphology and functional responses of cerebrovascular system in physiologic and pathologic conditions [61][62][63][64][65][66][67]. We and others have repeatedly shown that hypoxic-ischemic stress in newborn piglets severely attenuated CR to various so called "hypoxia-ischemia sensitive" stimuli determined in pial arterioles 1 hour after the insult [61,64,[68][69][70].…”
Section: Animal Models In Hie Researchmentioning
confidence: 99%
“…We and others have repeatedly shown that hypoxic-ischemic stress in newborn piglets severely attenuated CR to various so called "hypoxia-ischemia sensitive" stimuli determined in pial arterioles 1 hour after the insult [61,64,[68][69][70]. The attenuated CR showed spontaneous recovery, and it appeared intact as early as 4 hours after the ischemic insult [61,62,68,70].…”
Section: Animal Models In Hie Researchmentioning
confidence: 99%